Reciclagem de painéis fotovoltaicos e tecnologias de recuperação de materiais para geração de valor na cadeia e impactos ambientais - MARTINS, Glauber Sandi; YUKIMITSU, Guilherme Daiki (276, 2024)
A utilização da energia solar através de painéis fotovoltaicos/módulos fotovoltaicos constitui uma fonte limpa de energia tem se consolidado ao longo dos últimos anos. Esta afirmação tem como base, na maioria dos casos, a consideração apenas da geração de energia elétrica pelo painel após a sua fabricação e instalação. Há impactos em uma série de atividades dentro do processo de fabricação e que devem ser considerados. Em conformidade da matriz energética do país onde estas atividades são desenvolvidas, uma quantidade maior ou menor de emissões de CO2 ocorrerá, além de outros tipos de degradações ambientais. Desse modo, evidencia-se a necessidade de verificar, considerando-se a matriz energética do país onde o painel é fabricado e/ou reciclado, se é possível amortizar o gasto energético, as emissões de CO2 e as degradações causadas por seu processo de fabricação. A metodologia desta pesquisa consiste em um estudo de revisão da literatura, de caráter descritivo e exploratório; por ser um tipo de pesquisa muito específica, ela assume a forma de um estudo de caso. Utilizando-se de ferramentas de gestão ambiental, tais análises de ciclo de vida, energética e do passivo ambiental, pode-se estudar estes impactos desde a origem do painel até o término de seu tempo de vida útil. Assim, complementar a verificação da capacidade do módulo em amortizar das emissões de CO2, os impactos causados por sua fabricação, além de amortizar a energia elétrica gasta no processo. Se após a verificação, o painel ainda possuir tempo de vida útil para funcionar, ele poderá ser considerado como uma fonte limpa de energia. O objetivo da pesquisa foi realizar uma revisão sobre a produção e reciclagem dos módulos solares fotovoltaicos em seu ciclo de vida útil e respectivos impactos econômicos e ambientais. Como resultados foi possível fazer uma projeção de produção de resíduos, alertar para os impactos socioambientais causados por este crescimento, apresentar tecnologias de reciclagem e um levantamento simplificado dos dados relativos ao processo de análise de ciclo de vida e suas funções, o seu potencial de amortização do passivo ambiental gerado em sua fabricação, considerando todo o tempo de vida útil do painel fotovoltaico.

The use of solar energy through photovoltaic panels/photovoltaic modules constitutes a clean source of energy and has been consolidated over recent years. This statement is based, in most cases, on considering only the generation of electrical energy by the panel after its manufacture and installation. There are impacts on a series of activities within the manufacturing process that must be considered. Depending on the energy matrix of the country where these activities are carried out, a greater or lesser amount of CO2 emissions will occur, in addition to other types of environmental degradation. Therefore, it is necessary to verify, considering the energy matrix of the country where the panel is manufactured and/or recycled, whether it is possible to amortize the energy expenditure, CO2 emissions and degradation caused by its manufacturing process. . The methodology of this research consists of a literature review study, of a descriptive and exploratory nature; As it is a very specific type of research, it takes the form of a case study. Using environmental management tools, such as life cycle, energy and environmental liability analyses, these impacts can be studied from the origin of the panel until the end of its useful life. Thus, complementing the verification of the module's ability to amortize CO2 emissions, the impacts caused by its manufacturing, in addition to amortizing the electrical energy spent in the process. If, after verification, the panel still has useful life to function, it can be considered a clean source of energy. The objective of the research was to carry out a review of the production and recycling of photovoltaic solar modules in their useful life cycle and their respective economic and environmental impacts. As a result, it was possible to make a projection of waste production, highlight the socioenvironmental impacts caused by this growth, present recycling technologies and a simplified survey of data relating to the life cycle analysis process and its functions, its amortization potential. of the environmental liability generated in its manufacturing, considering the entire useful life of the photovoltaic panel.

ABSTRACT The use of solar energy through photovoltaic panels/photovoltaic modules constitutes a clean source of energy and has been consolidated over recent years. This statement is based, in most cases, on considering only the generation of electrical energy by the panel after its manufacture and installation. There are impacts on a series of activities within the manufacturing process that must be considered. Depending on the energy matrix of the country where these activities are carried out, a greater or lesser amount of CO2 emissions will occur, in addition to other types of environmental degradation. Therefore, it is necessary to verify, considering the energy matrix of the country where the panel is manufactured and/or recycled, whether it is possible to amortize the energy expenditure, CO2 emissions and degradation caused by its manufacturing process. . The methodology of this research consists of a literature review study, of a descriptive and exploratory nature; As it is a very specific type of research, it takes the form of a case study. Using environmental management tools, such as life cycle, energy and environmental liability analyses, these impacts can be studied from the origin of the panel until the end of its useful life. Thus, complementing the verification of the module's ability to amortize CO2 emissions, the impacts caused by its manufacturing, in addition to amortizing the electrical energy spent in the process. If, after verification, the panel still has useful life to function, it can be considered a clean source of energy. The objective of the research was to carry out a review of the production and recycling of photovoltaic solar modules in their useful life cycle and their respective economic and environmental impacts. As a result, it was possible to make a projection of waste production, highlight the socioenvironmental impacts caused by this growth, present recycling technologies and a simplified survey of data relating to the life cycle analysis process and its functions, its amortization potential. of the environmental liability generated in its manufacturing, considering the entire useful life of the photovoltaic panel. Keywords: Photovoltaic modules, Recycling, Energy.
Recycling of photovoltaic panels and material recovery technologies to generate value in the chain and environmental impacts
Keywords: Sistemas fotovoltaicos; Reciclagem; Gestão e Negócios